Climate change scenario: effects on agricultural productivity and economic impacts in the Brazilian state of Minas Gerais - Deborah Lopes Ferreira (2024)
This study investigates the future economic impacts of climate change in Minas Gerais, Brazil, using an econometric model and a Regional Computable General Equilibrium (CGE) model. Initially, the econometric model estimates variations in agricultural productivity due to climate factors for seven crops, based on regional climate scenarios from the Eta-CPTEC climate model. The scenarios considered are RCP 8.5 and RCP 4.5 from the 6th IPCC report. These estimates serve as productivity shocks in the CGE model, specifically IMAGEM-MG, developed from the Brazilian IMAGEM-B model and following the Australian TERM Model framework for disaggregated regional and sectoral analyses. The results reveal a distinct spatial pattern, with climatic effects on Minas Gerais’s economy varying significantly across regions. Generally, GDP and other key indicators would undergo reductions under both climate scenarios. Regions heavily dependent on agriculture, like Patos de Minas, would face the most significant deviations, while areas like Pouso Alegre, with less agricultural dependence and favorable conditions for crops like coffee, would experience the least reductions. Notably, the poorest regions are not necessarily the most affected by GDP reduction. Regions in the north and northeast of Minas, where agricultural activity is predominantly composed of small-scale farmers, may be severely impacted, exacerbating regional disparities. While most crops show productivity reductions, some regions would experience gains in specific crops, like sugarcane in Uberaba and Uberlândia and oranges in Barbacena. However, these gains do not offset the overall decline in economic activity compared to a scenario without climate change, likely due to spill-over effects on sectors dependent on agriculture.